FACTORS THAT ENCOURAGE SURABAYAâ€™S CITIZEN IN RESERVATION THROUGH OFFLINE TRAVEL AGENT (TRAVEL BUREAU) (Case Study on PT ANEKA TOURS AND TRAVEL SERVICES SURABAYA) - Irra Crisyanti Dewi; Heni Adhianata; Arnold Suwignyo (AIBPM Publisher, 2018)
This study want to know clearly about â€œThe factors that encourage Surabayaâ€™s citizen in making a reservation through offline travel agent (Travel Agency)â€ and the study was conducted at PT. Aneka Kartika Tours and Travel Services Surabaya. Which is the mainstay of this research is the rise of online business travel agent in Indonesia that make entrepreneurs of offline travel agents or travel agency must be competed. This competition aims to make travel agency can remain superior to online travel agents. However, although online travel agent has been growing rapidly but still found the customers who come and requires the existence of a travel agency. Therefore the aim of this study was to determine kind of factors that drive and influence Surabayaâ€™s citizen to continue to use the service of offline travel agents. There are four main variables used in this study that are marketing mix, psychological factors, situational factors and social factors. The method used in researching is confirmatory factor analysis, which it is apart of SEM (Structural Equation Modeling). The populations in this study are customers of PT. Aneka Kartika Tours and Travel Services Surabaya by distributing questionnaires to 120 customers, while the technique used is judgmental sampling. After distributing the questionnaire, the questionnaire results are calculated and processed using SPSS ver 21 and AMOS ver 21 thus it is produced a result that variable marketing mix, psychological factors, and situational factors are affected positively towards purchasing decisions through an offline reservation except on fourth variable that is social factors that should be eliminated because it has negative influence or do not contribute significantly.